2020
DOI: 10.1001/jamanetworkopen.2020.15707
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Positive Results on the Primary Care–Posttraumatic Stress Disorder Screen and Suicide Mortality Among US Veterans

Abstract: Key Points Question Are positive results on the Primary Care–Posttraumatic Stress Disorder Screen associated with an increase in the risk of suicide mortality among veterans receiving care in the US Veterans Health Administration system and, if so, does this risk decrease over time? Findings In this cohort study of 1 552 581 veteran patients receiving care in the US Veterans Health Administration system who were followed up through 2016, analyses of 1 693 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(119 reference statements)
2
19
0
Order By: Relevance
“…This is consistent with previous studies reporting the most pronounced risk elevation of suicide immediately after receiving a positive result on PTSD among US veterans. 17 Our results extend previous literature by showing similar decreasing trend of excess mortality across siblings discordant on all subtypes of stress-related disorders. Notably, acute stress reaction was associated with comparable or even greater risk of all-cause mortality, compared with PTSD and adjustment disorder, within the first year of follow-up, supporting the notion that acute and severe psychological symptoms after exposure to a traumatic event might lead to an immediately increased risk of death such as suicide.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with previous studies reporting the most pronounced risk elevation of suicide immediately after receiving a positive result on PTSD among US veterans. 17 Our results extend previous literature by showing similar decreasing trend of excess mortality across siblings discordant on all subtypes of stress-related disorders. Notably, acute stress reaction was associated with comparable or even greater risk of all-cause mortality, compared with PTSD and adjustment disorder, within the first year of follow-up, supporting the notion that acute and severe psychological symptoms after exposure to a traumatic event might lead to an immediately increased risk of death such as suicide.…”
Section: Discussionsupporting
confidence: 90%
“…As the elevation of mortality following a diagnosis of stress-related disorders may be time-dependent, 17 we first visualized the association of stress-related disorders with all-cause mortality by time since diagnosis using flexible parametric models. Because of the pronounced risk elevation during the first year after diagnosis (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that veterans whose symptoms satisfied the criteria for avoidance/numbing or hyperarousal and/or met the full diagnostic criteria were at increased risk for a future suicide attempt years later. These results highlight the clinical value of routine symptom screening in settings that reach large numbers of veterans (e.g., primary care; Cooper et al., 2020) and that suggest veterans whose symptoms satisfy any of these criteria warrant further suicide risk assessment. However, the observed poor specificity of these indicators indicates this approach would yield many false positives.…”
Section: Discussionmentioning
confidence: 75%
“…Although myriad factors contribute to the development and maintenance of suicidal thoughts and behaviors (Klonsky et al, 2016), research has repeatedly shown that individuals with elevated symptoms of posttraumatic stress disorder (PTSD) or a PTSD diagnosis are at increased risk for suicide (for reviews, see Holliday et al, 2020; Panagioti et al, 2009, 2012). More specifically, PTSD has been shown to predict suicidal ideation (Panagioti et al, 2017), suicide attempts (Stanley et al, 2019), and suicide mortality (Cooper et al, 2020). In fact, large-scale epidemiological investigations have demonstrated that PTSD is one of the few psychiatric disorders that predicts the transition from thinking about suicide to making a suicide attempt (Nock et al, 2009).…”
mentioning
confidence: 99%